Exploring CRISPR-Cas systems for precision food authentication: Molecular tools shaping the future of traceability and integrity - Hossain, M. A.Motalib; Mohamad, Nurhidayatul Asma; Mohd Desa, Mohd Nasir; Mustafa, Shuhaimi; Mohd Hashim, Amalia (Elsevier, 2026)
Ensuring the authenticity and traceability of food products is increasingly critical to combat food fraud, ensure consumer safety, and meet religious dietary requirements. Traditional nucleic acid (NA)-based methods like PCR provide high sensitivity but are restricted to laboratory environments, highlighting the need for portable alternatives. CRISPR-Cas systems have emerged as promising next-generation tools for food authentication due to their unique trans-cleavage activity, enabling efficient detection of NAs. Recent developments emphasize the integration of CRISPR-Cas with portable platforms such as lateral flow assays, nanopore sensors, smartphone-based devices, and microfluidic systems, which support rapid and reliable on-site detection of food contaminants. Moreover, the combination of CRISPR-Cas with advanced technologies could further enhance the reliability and innovation of food safety diagnostics. This review presents an overview of CRISPR-Cas mechanisms, classification, and advantages for NA detection, while also examining advancements in portable CRISPR-integrated systems for field applications. Additionally, it addresses current challenges, regulatory issues, and future directions, including multiplex detection, microfluidics integration, artificial intelligence applications, and eco-friendly diagnostic development. By consolidating these insights, the review provides valuable guidance for researchers, industry professionals, and policymakers, highlighting the transformative potential of CRISPR-Cas systems in advancing precision food authentication within the global supply chain.